Diagnosis of spondyloarthritis: Application of criteria in clinical practice - Sham Santhanam; Vinod Ravindran (Indian Journal of Rheumatology)
Spondyloarthritis (SpA) is an umbrella term for a group of inflammatory musculoskeletal conditions characterized by predominant involvement of the spine, the lower limb joints, and the entheses. The Assessment of SpA International Society (ASAS) group classifies SpA into axial SpA (axSpA) and peripheral SpA. axSpA was further divided into radiographic SpA and nonradiographic SpA. Classification criteria are meant for research purposes to enroll a homogeneous cohort, unlike diagnostic criteria, which are meant for diagnosing diseases in the community and therefore must include all the heterogeneous manifestations of a disease. Inflammatory low back pain is one of the most important features in history to be elicited in the diagnosis of axSpAs. It should not be used in isolation and always combined with other features of SpA. Magnetic resonance imaging (MRI) is the gold standard and is the only imaging modality capable of detecting both inflammatory and structural changes. A positive MRI finding should be interpreted in the relevant clinical context, and an alternative differential diagnosis for sacroiliitis should be considered if the clinical picture is atypical of SpA. The presence of HLA B 27 in isolation is neither diagnostic of SpAs nor its absence rules out the diagnosis. Erythrocyte sedimentation rate and C-reactive protein are the commonly used biomarkers in SpA but do not always correlate with disease activity. The ASAS criteria have been tested for its validity, though there were concerns regarding its specificity. In this narrative review various criteria available for classifying SpAs have been discussed and their strengths, weaknesses, and usefulness in the diagnosis of SpA in our everyday practice have been appraised . Various referral strategies and usefulness of these criteria and parameters in the Indian context have also been discussed.